Free Flap Evaluation Following Reconstruction of Locally Advanced Squamous Cell Carcinoma of The Tongue - Atmodiwirjo, Parintosa; Kartini, Dian; Arina, Maryam Nur; Sapphira, Elrica; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester (Jurnal Plastik Rekonstruksi, 2023)
Background: Neoadjuvant chemotherapy (NAC) is a crucial component in the management of tongue-based locally advanced squamous cell carcinoma (LASCC) due to its ability to decrease tumor mass and facilitate free tissue transplantation. The utilization of adjuvant radiation and chemotherapy has been observed to decelerate the progression of post-operative tumor growth. Probability of free flap failure is elevated. Post-operative complications and the long-term functional outcomes of speaking, salivation, and swallowing determine the quality of free flaps.Methods: A retrospective review of tongue LASCC patients who underwent NAC followed by glossectomy and free tissue transfer from 2015 to 2018. Tongue functional outcomes of speaking, swallowing, and salivation were assessed using FACE-Q scale in 3 times follow-up period.Result: This study included 7 patients who underwent tongue reconstruction. Treatment modalities were based on tumor presentation, with 4 patients (57.1%) receiving Taxane, 5-Fluorouracil, and Paclitaxel/Doclitaxel (TPF), and 3 patients (42.1%) receiving Paclitaxel and 5-Fluorouracil (PF). Tongue reconstruction utilized the radial forearm free flap in 5 patients (71.4%) and the anterolateral thigh free flap in 2 patients (28.6%). Intraoperatively, NAC had no impact on the integrity of small and reliable donor vessels. Three patients died from tumor metastases after the second follow-up assessment, while one patient was lost to follow-up. The study found no significant association between chemotherapy dosage and free flap vitality (P = 0.629). FACE-Q assessments revealed moderate to low scores in speaking, eating, and drinking outcomes.Conclusion: Tongue reconstruction after NAC in LASCC patients remains a challenging procedure for surgeons. While the consideration of surgical difficulties due to damage of the donor vessels demands a more structured pre-operative plan. No correlation between the exposure of NAC or AR to free flap complication as well as functional outcome.